What Effect Will East Asia's Crisis Have on Developing Countries? - Dadush, Uri; Lynn, Robert; Riordan, Mick; Dasgupta, Dipak; Johannes, Ronald (World Bank, Washington, DC, 2012)
This note summarizes recent projections on the longer-term effects of the East Asia's financial crisis, and the significant effect already felt in developing countries. Five main points are examined, as follows: 1) though trade will drive the recovery, adjustment will be deep and protracted, in the region, mostly in Indonesia, Korea, Malaysia, the Philippines and Thailand; 2) developing countries will be mostly affected, since reductions in growth are estimated to double due to high trade multipliers, terms of trade movements, as well as tight monetary and fiscal policies in those countries relying on private capital flows; 3) because of lower oil prices, oil importing countries stand to lose the most, with Latin America, the Middle East, and North and Sub-Saharan Africa the hardest hit; 4) the crisis will bear a significant effect on the world economy, though not nearly as damaging as the 1973 and 1978 oil shocks; and 5) increased risks, such as a spillover or cutoff in credit, for developing countries are estimated, though predicted to be manageable.